Kandungan Protein Kasar dan Serat Kasar Pada Kulit Pisang Raja yang Difermentasi dengan Trichoderma viride dan Bacillus subtilis sebagai Bahan Baku Pakan Ikan [ Crude Protein And Fiber Content Of Rough Of Fermented On The King Banana Skins By Trichoderma viride And Bacillus subtilis As Raw Fish Feed] - Agustono Agustono; Mohamad Yusuf; Dewa Ketut Meles (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Utilization of fish waste as an alternative feed ingredient in the effort to increase the availability of raw materials making up rations. Banana skin is one that has the potential of agricultural waste into alternative feed ingredients, but the nutritional value contained in the banana peel is still low so we need to attempt to improve nutritional content, one of which is fermentation method using Trichoderma viride and Bacillus subtilis in order to improve crude protein and lower content of crude fiber on a banana peel. This study aims to determine the influence of Trichoderma viride on crude protein and crude fiber are fermented banana skin, know the effect of Bacillus subtilis on crude protein and crude fiber are fermented banana skin and know the effect of interaction of Trichoderma viride and Bacillus subtilis of crude protein and fiber fermented banana skin rough. This research method is to experiment with Completely Randomized Design (CRD) as a factorial experimental design. The treatments used consisted of two factors, namely the effect of Trichoderma viride (factor A) and Bacillus subtilis (factor B). Factor A consisted of three dose levels: 0%, 3% and 6%, while factor B consists of three levels ie dose of 0%, 4% and 8%. Each treatment combination was replicated 3 times. The results showed that the use of Trichoderma viride and Bacillus subtilis in fermentation processes plantain skin showed significant differences on crude protein and crude fiber on dry matter (p<0.05).